PERSONALIZED MEDICINE IN NEUROLOGY: INTEGRATING GENOMICS, ARTIFICIAL INTELLIGENCE, AND MULTIMODAL CLINICAL DATA FOR PRECISION DIAGNOSIS AND TREATMENT (Global Conference on Medical and Health Sciences, 2026)
Personalized medicine in neurology represents a paradigm shift from traditional one-size-fits-all approaches toward data-driven, patient-specific diagnosis and treatment strategies. The integration of genomics, artificial intelligence (AI), and multimodal clinical data has significantly enhanced the ability to understand the heterogeneity of neurological disorders and to tailor interventions based on individual biological profiles. Advances in high-throughput sequencing, neuroimaging, and computational analytics are enabling more precise characterization of disease mechanisms and progression.
Keywords: Personalized medicine; Neurology; Genomics; Artificial intelligence; Precision medicine; Neuroimaging; Biomarkers; Data integration